2019
DOI: 10.32793/jrdi.v3i2.488
|View full text |Cite
|
Sign up to set email alerts
|

Temuan insidental lesi radiopak asimptomatik pada pemeriksaan radiografi panoramik: laporan 3 kasus dan ulasan pustaka Dense Bone Island (DBI)

Abstract: Objectives: Dense Bone Island (DBI) is one of the lesions that are usually visualized on a panoramic radiographs in the form of total radiopaque in the periapical area of the mandibular premolar or molar but most of them are not directly related to the dentition. This case report is aimed to give summaries about the description of 3 DBI cases. Case Report: Three panoramic radiographs of patients with asymptomatic well-defined radiopaque lesions which was found incidentally in the periapical area of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(15 reference statements)
0
5
0
1
Order By: Relevance
“…8,15 Lesi idiopathic osteosclerosis secara mekanisme penyakit merupakan lesi dengan pertumbuhan terlokalisir dari tulang kompakta dalam struktur tulang trabekular atau kanselus sehingga terjadi pelebaran tulang trabekular dan meluas hingga ke ruang medular dan kemunculan lesi idiopathic osteosclerosis bersifat sklerotik soliter. 16 Gambaran radiografi lesi pada kasus yang dilaporkan adalah radioopak dengan batas jelas dengan bentuk tidak beraturan (irregular), hal tersebut serupa dengan gambaran radiografi yang didapatkan pada penelitian yang dilakukan oleh Farhadi dkk (2016) yang menemukan bahwa bentuk idiopathic osteosclerosis yang paling banyak adalah irregular yaitu sebanyak 40,6% dan diikuti dengan bentuk oval sebanyak 31,3%, dan bentuk yang paling sedikit ditemukan adalah bentuk bulat yaitu sebanyak 28,1%. 6 Hal serupa juga ditemukan pada beberapa penelitian yang menunjukkan bahwa lesi idiopathic osteosclerosis paling banyak berbentuk irregular dan diikuti dengan lesi berbentuk bulat.…”
Section: Discussionunclassified
“…8,15 Lesi idiopathic osteosclerosis secara mekanisme penyakit merupakan lesi dengan pertumbuhan terlokalisir dari tulang kompakta dalam struktur tulang trabekular atau kanselus sehingga terjadi pelebaran tulang trabekular dan meluas hingga ke ruang medular dan kemunculan lesi idiopathic osteosclerosis bersifat sklerotik soliter. 16 Gambaran radiografi lesi pada kasus yang dilaporkan adalah radioopak dengan batas jelas dengan bentuk tidak beraturan (irregular), hal tersebut serupa dengan gambaran radiografi yang didapatkan pada penelitian yang dilakukan oleh Farhadi dkk (2016) yang menemukan bahwa bentuk idiopathic osteosclerosis yang paling banyak adalah irregular yaitu sebanyak 40,6% dan diikuti dengan bentuk oval sebanyak 31,3%, dan bentuk yang paling sedikit ditemukan adalah bentuk bulat yaitu sebanyak 28,1%. 6 Hal serupa juga ditemukan pada beberapa penelitian yang menunjukkan bahwa lesi idiopathic osteosclerosis paling banyak berbentuk irregular dan diikuti dengan lesi berbentuk bulat.…”
Section: Discussionunclassified
“…3,12 The formation of micronucleus in exfoliated buccal mucosa cells after exposed to panoramic radiograph was found in several research that conducted by Cerqueira et al Their publication showed that there was a significant increase in the amount of micronucleus in exposed group. [12][13][14][15][16][17] The increase in the number of micronucleus indicated a genomic instability and was thought to be associated with an increase in carcinogenic effects. The differences in the micronucleus of the samples in the same group could be caused by chromosome alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of DBI are discovered incidentally during radiographic examinations, such as periapical and panoramic radiographs that are performed to diagnose other diseases. 1,2 Panoramic radiography is one of the most frequently used radiographic techniques in dentistry which produces an overall view of the maxilla and mandible as well as surrounding tissues and are used as a first step to detect and obtain information for further treatment steps. 3 Therefore, panoramic radiographs can be used to see the presence of DBI in the jaw.…”
Section: Introductionmentioning
confidence: 99%
“…DBI can also be thought of as a type of bone development that is unrelated to local stimuli. 2,4 On the radiograph, DBI appears as a localized radiopaque mass with well-defined boundaries. 5 DBI can be round, elliptical, or irregular in shape, varying in size from 2-3 mm to 1-2 cm in diameter and unrelated to tooth vitality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation